Factor(s) in the culture medium of a slime strain which stimulate DNA uptake. - M. Schablik; B. Kocsar; G. Szabo (Fungal Genetics Reports, 1980)
Factor(s) in the culture medium of a slime strain which stimulate DNA uptake.